Case Report: Severe McCune–Albright syndrome presenting with neonatal Cushing syndrome: navigating through clinical obstacles - Unsal, Yagmur; Gozmen, Onur; User, İdil Rana; Hızarcıoglu, Hayriye; Gulhan, Bora; Ekinci, Saniye; Karagoz, Tevfik; Ozon, Z. Alev; Gonc, E. Nazlı (Frontiers in Endocrinology, 2023)
Background: Cafe au-lait skin macules, Cushing syndrome (CS), hyperthyroidism, liver and cardiac dysfunction are presenting features of neonatal McCune Albright Syndrome (MAS); CS being the rarest endocrine feature. Although spontaneous resolution of hypercortisolism has been reported, outcome is usually unfavorable. While a unified approach to diagnosis, treatment and follow-up is lacking, herein successful treatment and long-term follow-up of a rare case is presented.Clinical Case: An 11-day-old girl born small for gestational age presented with deterioration of well-being and weight loss. Large hyperpigmented macules on the trunk, hypertension, hyponatremia, hyperglycemia, and elevated liver enzymes were noted. ACTH-independent CS due to MAS was diagnosed. Although metyrapone (300 mg/m 2 /day) was started on 25 th day, complete remission could not be achieved despite increasing the dose up to 1850 mg/m 2 /day. At nine months, right total and left three quarters adrenalectomy was performed. Cortisol decreased substantially, ACTH remained suppressed, rapid tapering of hydrocortisone to physiological dose wasn't tolerated, and supraphysiological doses were required for two 2 months. GNAS analysis from adrenal tissue showed a pathogenic heterozygous mutation.During 34-months of follow-up, in addition to CS due to MAS, fibrous dysplasia, hypophosphatemic rickets and peripheral precocious puberty were detected. She is still regularly screened for other endocrinopathies.Neonatal CS due to MAS is extremely rare. Although there is no specific guideline for diagnosis, treatment or follow-up, addressing side effects and identifying treatment outcomes will improve quality of life and survival.